Acceptance of Using Cricket Flour as a Low Carbohydrate, High Protein, Sustainable Substitute for All-Purpose Flour in Muffins. Issue 3 (3rd May 2020) - Burt, Kate G.; Kotao, Takumi; Lopez, Isimar; Koeppel, Jamie; Goldstein, Avia; Samuel, Lalitha; Stopler, Marina
ABSTRACT: Our aim is to assess the nutritive value and acceptability (enjoyment, palatability, and desirability) of a cricket flour (CF) muffin compared to an all-purpose flour (AP) muffin. Participants (n = 198) completed a blind taste test and survey about demographics, muffin characteristics, and attitudes toward food products. Scores for enjoyment did not differ significantly but scores were significantly higher for the texture of the CF muffin. Rejection of crickets emerged as a primary reason for low desirability of CF muffins. These findings indicate that CF may be used to create an enjoyable muffin but one that may not be widely accepted.